Interrelation between homocysteine metabolism and the development of autism spectrum disorder in children - Li, Bingbing; Xu, Yiran; Pang, Dizhou; Zhao, Qiang; Zhang, Lingling; Li, Ming; Li, Wenhua; Duan, Guiqin; Zhu, Changlian (Frontiers in Molecular Neuroscience, 2022)
Evidence is emerging that dysregulation of the circulating concentrations of homocysteine, an important intermediate in folate and vitamin B12 metabolism, is associated with autism spectrum disorder (ASD), but comprehensive assessments and correlations with disease characteristics have not been reported. Multivariate ordinal regression and restricted cubic splines (RCS) models were used to estimate the independent correlations between serum homocysteine, folate, and vitamin B12 levels and clinical outcomes and severity of children with ASD. After adjusting for confounding factors, serum homocysteine levels were significantly higher in children with ASD than healthy controls (β: 0.370; 95% CI: 0.299 0.441, p < 0.001). Moreover, homocysteine had a good diagnostic ability for distinguishing ASD from healthy subjects (AUC:0.899, p < 0.001). The RCS model indicated a positive and linear association between serum homocysteine and risk of ASD. The lowest quartile of folate was positively associated with ASD severity (OR: 4.227, 95% CI: 1.022 17.488, p = 0.041) compared to the highest quartile, and serum folate showed a negative and linear association with ASD severity. In addition, decreased concentrations of folate and vitamin B12 were associated with poor adaptive behavior developmental quotients of the Gesell Developmental Schedules (p < 0.05). Overall, increased homocysteine level was associated with ASD in a linear manner and is thus a novel diagnostic biomarker for ASD. Decreased concentrations of folate and vitamin B12 were associated with poor clinical profiles of children with ASD. These findings suggest that homocysteine-lowering interventions or folate and vitamin B12 supplementation might be viable treatment strategies for ASD.